Molecular and morphological signatures for extreme environmental adaptability of the invasive mussel Brachidontes pharaonis (Fischer, 1870). (October 2020) - Mohammed-Geba, Khaled; Sheir, Sherin K.; El-Aziz Hamed, Elsayed Abd; Galal-Khallaf, Asmaa
Abstract: Brachidontes pharaonis (Bivalvia:Mytilidae) is one of the most successful Lessepsian migrants. Its extensive populations' expansion and phenotypic plasticity might reshape the Mediterranean biodiversity. Individuals of B. pharaonis were collected from various sites in the Mediterranean Sea and the Red Sea in Egypt. Species-specific primers for Cytochrome Oxidase Subunit 1 gene were designed. They were applied for analysis of mussel's population genetics and assessment of its aquatic environmental DNA (eDNA) abundance. Morphological, allometric and morphometric characteristics were also described. The newly designed primers could efficiently detect the species presence, abundance, and genetic diversity. The Northern Red Sea and north-westward populations exhibited higher nucleotide diversities than southwards. Phylogeny and principal coordinates' analysis (PCoA) detected three geographical categories for B. pharaonis : one of the Indian Ocean, other of the Middle Red Sea and southwards, and the other extends from the Northern Red Sea to the westernmost part of the Mediterranean. Intraspecific differences in the shell shape, colour, and biometrics were noted. The shells were significantly smaller and lighter in rocky habitats than in sandy ones. The morphometric indices and allometry were significantly different between rocky and sandy environments. In general, B. pharaonis genetic and morphological features appeared to contribute much to the species success in versatile habitats. Highlights: Brachidontes pharaonis is an active mollusc in reshaping the Mediterranean environment. It exhibits differential morphologies, making it sometimes mistaken with other mussels. Its population genetics have been analysed in different Mediterranean and Red Sea locations. Morphological, allometric and morphometric characteristics were assessed for that mussel. The versatile genetic and morphological features of B. pharaonis support its future spread in the Mediterranean region.